Identification of Anaplasma marginale, Babesia bovis and Babesia bigemina resistance alleles in Crioulo Lageano cattle using PCR-SBT and BoLA-DRB3 gene sequencing - Casa, Mariana da Silva; Giovambattista, Guillermo; Fonteque, Graziela Vieira; Miguel, Ellen Lara; Vogel, Carla Ivane Ganz; Miletti, Luiz Claudio; Takeshima, Shin-Nosuke; Fonteque, Joandes Henrique (Frontiers in Veterinary Science, 2023)
The BoLA-DRB3 gene in cattle is associated with tolerance to several infectious diseases, such as neosporosis, dermatophilosis, leukosis, and mastitis. This study used PCR-SBT and BoLA-DRB3 gene sequencing to determine the association between the presence or absence of Anaplasma marginale, Babesia bovis, and B. bigemina infections in 208 Crioulo Lageano cattle and alleles present in the population. The chi-square test and odds ratio analysis were employed to establish the association. Of the BoLA-DRB3 gene alleles present in the population, two alleles were significantly associated with resistance to A. marginale infections: BoLA-DRB3001:01 (p<0.001; OR=0.224), which had a frequency of 7.93%, and BoLA-DRB3024:06 (p=0.007; OR<0.00001), which had a frequency of 0.72%. Regarding B. bovis infection, the BoLA-DRB3*011:01 allele (p=0.002; OR=0.271) had a frequency of 6% in the population and was associated with resistance to the infection. None of the alleles was associated with resistance to infection by B. bigemina. Therefore, the Crioulo Lageano breed has alleles that may confer resistance against infection by A. marginale and B. bovis.